A randomised controlled trial of Caphosol mouthwash in management of radiation-induced mucositis in head and neck cancer. Issue 2 (February 2017) - Wong, Kee H.; Kuciejewska, Aleksandra; Sharabiani, Mansour T.A.; Ng-Cheng-Hin, Brian; Hoy, Sonja; Hurley, Tara; Rydon, Joanna; Grove, Lorna; Santos, Ana; Ryugenji, Motoko; Bhide, Shreerang A.; Nutting, Chris M.; et al.
Abstract: Purpose: This phase III, non-blinded, parallel-group, randomised controlled study evaluated the efficacy of Caphosol mouthwash in the management of radiation-induced oral mucositis (OM) in patients with head and neck cancer (HNC) undergoing radical (chemo)radiotherapy. Patients and methods: Eligible patients were randomised at 1:1 to Caphosol plus standard oral care (intervention) or standard oral care alone (control), stratified by radiotherapy technique and use of concomitant chemotherapy. Patients in the intervention arm used Caphosol for 7 weeks: 6 weeks during and 1-week post-radiotherapy. The primary endpoint was the incidence of severe OM (CTCAE ⩾grade 3) during and up to week 8 post-radiotherapy. Secondary endpoints include pharyngeal mucositis, dysphagia, pain and quality of life. Results: The intervention ( n = 108) and control ( n = 107) arms were well balanced in terms of patient demographics and treatment characteristics. Following exclusion of patients with missing data, 210 patients were available for analysis. The incidence of severe OM did not differ between the intervention and control arms (64.1% versus 65.4%, p = 0.839). Similarly, no significant benefit was observed for other secondary endpoints. Overall, compliance with the recommended frequency of Caphosol was low. Conclusion: Caphosol did not reduce the incidence or duration of severe OM during and after radiotherapy in HNC.